Vibrations of a Complex System with a Viscoelastic Inertial Interlayer - Cabanska-Placzkiewicz, K. (Проблемы прочности, 2001)
The paper presents an analytical method for solving problems of free and forced vibrations with damping of complex systems whose loaded layers are made of homogeneous elastic inertial materials, and the middle one is made of viscoelastic inertial material. Small lateral vibrations of the complex systems are caused by distributed and movable loads. A dynamic analysis of laminated structures for a wide range of variation of the geometrical and mechanical characteristics of a layer from viscoelastic inertial material was performed.